Genetic Variation of Porang (Amorphophallus muelleri Blume) After Mutation Induction Using Colchicine - Wahyudi, Didik; Putri, Amalia Nasyira; Resmisari, Ruri Siti; Suyono, Suyono (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Porang (Amorphophallus muelleri Blume) is a tuberous plant with the highest glucomannan among Amorphophallus genera. However, the low genetic diversity of porang today can affect porang cultivation in the future. Therefore, increasing the genetic diversity of porang by polyploidy induction using colchicine is needed. 30 days after planting porang shoot explants were used for polyploidy induction. After polyploidy induction using colchicine, DNA was extracted using Geneid Genomic DNA Mini Kit. Genetic diversity and clustering analysis was performed to assess the genetic diversity of porang after mutation induction. Mutation induction using colchicine successfully increased the genetic diversity of porang. Polyploidy induction using 0.05% colchicine is recommended to increase genetic variation of porang.